MOBILE RESEARCH INDUSTRY INSTALLATION OF WASTE CLEANING OF INDUSTRIAL AND DOMESTIC WASTE FROM TOXIC SUBSTANCES WITH USE OF OZONE AND ULFRAPHYOLETE RADIATION - Nazarenko, I. I.; Chaliapin, S. M.; Chaliapina, T. S. (Техніка будівництва, 2020)
The high efficiency of the mobile installation for the solution of global environmental problems and the elimination of anthropogenic technological factors has been proved. The efficiency of the unit for detoxification of sewage is shown, which can be used for the disposal of toxic waste from household and industrial wastes, sewage of chemical and pharmaceutical enterprises, utilization of outdated pesticides and mineral fertilizers that have become unfit for the disposal of unfit medicines, etc.